2014
DOI: 10.1111/jgh.12541
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25‐hydroxyvitamin D concentrations associate with non‐alcoholic fatty liver disease in adolescents independent of adiposity

Abstract: . (2014) Low serum 25-hydroxyvitamin D concentrations associate with non-alcoholic fatty liver disease in adolescents independent of adiposity.Journal of Gastroenterology and Hepatology, 29 (6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
4
51
1
Order By: Relevance
“…Because fatty liver is associated with low serum 25(OH)D concentration [46, 47], we measured hepatic fat and found that liver fat did not differ among diet groups. However, there was an up-regulation of Cyp2r1 protein expression in the MUFA group despite an absence of fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…Because fatty liver is associated with low serum 25(OH)D concentration [46, 47], we measured hepatic fat and found that liver fat did not differ among diet groups. However, there was an up-regulation of Cyp2r1 protein expression in the MUFA group despite an absence of fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of vitamin D insufficiency have been identified in pediatric NAFLD (114116), but there are no trials in children evaluating vitamin D supplementation as a treatment for NAFLD. In a small study of ursodeoxycholic acid in children, diet alone compared to ursodeoxycholic acid plus diet or ursodeoxycholic acid without diet did not show any benefit of the drug (117).…”
Section: Treatment Of Nafld In Childrenmentioning
confidence: 99%
“…Recently, vitamin D deficiency (VDD) has been associated with obesity, metabolic syndrome and cardiovascular risk in adults and children [13]. VDD occurs frequently among healthy children, with a rate of 55% in the American pediatric population [14].…”
Section: Introductionmentioning
confidence: 99%